Computational modeling for enhanced reliability in space missions: An integrated FAHP-COPRAS approach to supplier selection - Bo-Yu Lin; Hsiaoping Yeh (PLoS ONE, 2025)
Liquid Crystal Displays (LCDs) are indispensable in space science, playing critical roles in spacecraft instrumentation, data visualization, and control systems. Selecting reliable suppliers for LCD equipment is vital to ensuring optimal performance and durability in the challenging conditions of outer space. This paper presents a comprehensive decision-making framework using fuzzy multi-criteria decision-making (MCDM) methodologies tailored for aerospace applications. The framework begins with the Fuzzy Analytic Hierarchy Process (FAHP) to determine criteria weights such as technical specifications, environmental resistance, quality and reliability, cost and delivery performance, compliance, and certifications. These criteria are crucial for meeting the stringent requirements of space missions and reflect objective metrics and expert opinions. Subsequently, the Complex Proportional Assessment of Alternatives (COPRAS) is applied to rank potential suppliers based on their performance against the weighted criteria. COPRAS allows for a comparative analysis considering positive and negative preferences, ensuring suppliers meet technical specifications and align with strategic mission objectives and constraints. Integrating FAHP and COPRAS enhances supplier selection processes’ transparency, consistency, and objectivity in aerospace procurement. This approach mitigates the risks associated with supplier variability, ensuring continuity in operations critical to space exploration and scientific advancements. The study contributes to advancing decision support systems in aerospace procurement, emphasizing rigorous supplier evaluation methodologies to enhance mission success and reliability in space science applications.